Challenges of Philology in the Age of AI: How Artificial Intelligence is Changing ESL-Teaching, Translation and Research - Zmiiova , Iryna; Panenko , Inna; Huslenko , Iryna; Karpenko , Olena (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article analyses the impact of artificial intelligence (AI) on the main areas of philological activity. The relevance of the topic is stipulated by the need to rethink traditional approaches to teaching, translation and research in the context of technological transformations. The object of the study is artificial intelligence and its technologies in the educational domain, and the subject is the ways of applying them in teaching, translation and research. The article aims to provide a comprehensive analysis of the impact of AI on three main areas of philological activity: ESL teaching, translation and research. To achieve this goal, the authors analyse modern AI tools used in ESL teaching; investigate the impact of AI on translation theory and practice; identify the benefits and risks of using AI in research; and outline the ethical and regulatory aspects of using AI in the philological field. The article takes a comprehensive look at the use of AI in teaching English as a foreign language, including such tools as adaptive platforms, chatbots, personalised assessment, and the transformation of the role of the teacher and the structure of the course. In the field of translation, the evolution of CAT tools, the growing role of post-editing and the threat of losing professional skills are analysed. Special attention is paid to AI’s impact on research methodology, including the ease of access to information, automated source analysis, and text editing. The final section is focused on the ethical and academic aspects of using AI, including issues of integrity, authorship, and academic responsibility.